A scale for seventh and eighth grade students’ attitudes towards skill-based mathematics questions - Erhan, Gönül; Doğan, Oğuzhan; Haser, Çiğdem (Mehmet Tekerek, 2025)
The aim of this study is to develop a theoretically sound, valid, and reliable scale to examine seventh and eighth grade students’ attitudes towards so-called skill-based mathematics questions (SBMQ). The sample of the study was 820 seventh and eighth grade students at three different middle schools in Etimesgut District of Ankara Province. A draft item pool was crafted after a detailed literature review and the scale was finalized for the implementation after receiving expert opinions. This version of scale was administered shortly before the national examination which included skill-based questions in the 2022-2023 academic year. Exploratory and confirmatory factor analysis methods were used to examine the construct validity of the scale. The analysis resulted in 16 items in three factors (affective, cognitive, and motivational) which explained 46% of the total variance. Cronbach’s alpha and composite reliability scores were above .70 for each factor and whole scale. The results indicated that the Attitudes Towards SBMQ Scale developed for seventh and eighth grade students is valid and reliable.